A new species of Microphallus (Trematoda: Microphallidae) from Venezuela - Díaz, M T (2004)
During 1997-1999, a total of 94 crabs, Uca rapax were collected from La Sabana, La Ceiba and El Paujil, Sucre State, Venezuela. Of these 36 were infected with metacercariae. Two parasites were located in the abdominal muscles and one under the tissue of carapace and gonad. These metacercariae grew to adults in the following genera: Levinseniella, Microphallus and Maritrema, in the period of 2-5 days after feeding experimentally to the rat Rattus norvegicus, mice Mus musculus and duck Cairinia moschata. Specimens of the genus Microphallus were described herein as a new species M. sabanensis. The life cycle of M. sabanensis sp.nov. were studied experimentally using rat, mice and duck. All developmental stages and the adult are described. In addition, M. sabanensis was collected from wild birds Anas discors, Pluvialis squatarola, Butorides striatus, Egretta caerulea and Nycticorax violaceus from the same localities.